2003
DOI: 10.1017/cbo9780511667312
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning in Distance Education

Abstract: Distance learning presents language teachers and learners with a new set of challenges, opportunities and practical realities. This book presents a comprehensive overview of important issues within the field and explores the ways in which all participants are adapting their practices in response to the new learning environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(142 citation statements)
references
References 0 publications
0
133
0
9
Order By: Relevance
“…The adequacy of resources to support the use of the CALL activity Teles, & Turoff, 1997;Hauck & Haezewindt, 1999;Lynch, 2002;White, 2003). Instead, this literature review looks at online language learning as a system, and the role of the teacher as one of the stakeholders in the learning process.…”
Section: Language Learning Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…The adequacy of resources to support the use of the CALL activity Teles, & Turoff, 1997;Hauck & Haezewindt, 1999;Lynch, 2002;White, 2003). Instead, this literature review looks at online language learning as a system, and the role of the teacher as one of the stakeholders in the learning process.…”
Section: Language Learning Potentialmentioning
confidence: 99%
“…Online language learning has steadily increased in popularity over the last decade with the growth of the internet and the proliferation of computers at home and in educational settings ranging from K-12 to post-secondary (Felix, 2003a;Hubbard & Levy, 2006;Stickler & Hauck, 2006a;White, 2003). White (2003) indicated that there were more than 1300 distance language courses from the 55,000 distant courses registered in 130 countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In her book, White (2004) looked ahead towards new teaching and learning spaces, believing that this "involves a complete rethinking of all aspects of practice, for all participants. It means working with an interconnected community of learners, using a number of new media […] and it means higher levels of interaction and collaboration, which in turn require particular kinds of skills, motivation and commitment."…”
Section: Resultsmentioning
confidence: 99%
“…The concepts of autonomy and self-regulation do not suggest a state of independence on the part of the learner, but rather reflect the idea of collaborative control, in which teachers help learners build competencies and capacity through strategy training and task management (White, 2003). Autonomy involves both choice of what, when and how to learn and capacity for taking responsibility (Holec, 1981;Little, 1991;Hurd, 1998Hurd, , 2005White, 2003). SRL focuses predominantly on how to learn (Andrade & Evans, 2012) and, as such, was the focus of instructional materials in the course upon which this study is based.…”
Section: Theoretical Approachmentioning
confidence: 99%